Unusual optical isotropy in anisotropic alkali metal perchlorates MClO4 (M = Li, Na, K, Rb, Cs). (2nd November 2018) - Jharapla, Prathap Kumar; Narsimha Rao, Elaprolu; Vaitheeswaran, G
Abstract: We report a detailed study on structural, vibrational, born effective charge (BEC), electronic and optical properties of the alkali metal perchlorates, M ClO 4 (M = Li, Na, K, Rb, Cs) based on Density functional theory. The ground state calculations are done using plane wave pseudopotential method by including dispersion corrected method for more accurate prediction of structural and vibrational frequencies. The calculated lattice parameters and bond lengths are consistent with the experimental values. Further, detailed interpretation of the zone centered vibrational modes yields good concurrence between the experimental and calculated values. There is a decrease in wavelength with an increase in frequency (blue shift) from Li → Na → K → Rb → Cs. The obtained BEC shows the mixed covalent-ionic character of the compounds. The electronic and optical properties are calculated using the full potential linearized augmented plane wave method by TB-mBJ potential. The TB-mBJ band structure shows indirect band gap with O- 2p states dominating in the valence band. In spite of anisotropic structure, alkali metal perchlorates are found to possess optical isotropy.